KAJIAN KESESUAIAN LARVA HERMETIA ILLUCENS (DIPTERA: STRATIOMYIDAE) PADA PERBANYAKAN NEMATODA ENTOMOPATOGEN STEINERNEMA SPP. SECARA IN VIVO - Muhlison, Wildan; Purnomo, Hari; Saputra, Tri Wahyu (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2022)
Entomopathogenic nematodes (EPN) are parasites that are effective in controlling plant pests that can be propagated in vivo. In vivo propagation requires a host because EPN is an obligate parasite, one of which is the larvae of Hermetia illucens (Diptera: Stratiomyidae). These larvae are easy to obtain, easy to cultivate, easy to use, have a short life cycle, and have a high nutritional content. This study aimed to examine the suitability of H. illucens larvae in the entomopathogenic nematode Steinernema spp. in vivo propagation. This research was conducted by examining the mortality rate and infection rate of EPN in H. illucens larvae with variations in wounds, concentrations of infective nematodes, and larval size. The test results were compared with the larvae of T. molitor which are commonly used as hosts. The results of the mortality rate study showed that injured H. illucens larvae were more susceptible to the entomopathogenic nematode Steinernema spp.. There was a significant difference in mortality rates between uninjured and injured although there was no difference in results due to variations in EPN concentrations. The infection rate test showed a significant difference in wound variation and larval size of H. illucens although the results were not good enough when compared to the level of infection of T. molitor larvae. Keywords: Hermetia illucens, Tenebrio molitor, Steinernema spp., Entomopathogenic nematodes, In vivo